EFFECT OF SCHISTOSOMA HAEMATOBIUM INFECTION AND DRUG TREATMENT ON THE IMMUNE SYSTEM OF IMMUNOSUPPRESSED GUINEA PIGS (FUDMA JOURNAL OF SCIENCES, 2023)
Guinea pigs were immunosuppressed, before infection with S. haematobium. They were treated with different drug combination (Artequine, Artemether and Praziquantel), to ascertain their efficacy. The Guinea pigs were acclimatized to laboratory conditions for a week prior infection with 200 S. haematobium cercariae. Male and female guinea pigs weighing 2.5–6.5 kg were divided into four groups, 1- 4 (with 36-42 guinea pigs each). They were further divided into twelve subgroups of A - L with 3-4 guinea pigs each. The grouping 1-4 was done to monitor the effect of the drugs after 2, 7, 28 and 90 days post infection on the haematological parameter. Blood sample for Differential White Blood Cell (WBC) were collected using orbital technique from the retrobulbar plexus of the medial canthus of the eye of the guinea pigs, before analysis. Infection with S. haematobium (Before) decreased the level of lymphocyte when compared with normal control (NC) two days post infection. Except for treatment (After) with 75mg/kg Praziquantel PZQ and 100/200 mg/kg PZQ/ART, all other treatment regimen decreased the level of lymphocyte seven days post infection. Eosinophilia was observed after infection when compared with the NC, hence the mean level of eosinophil decreases after treatment (eosinopenia). Infection with S. haematobium increased the level of eosinophil, treatment with 75 and 300 ART and PZQ further increased the level of eosinophil seven days post infection. Infection with S. haematobium caused eosinophil in some of the animal and treatment further elevated the value of eosinophil
Keywords: Guinea pigs, Schistosoma haematobium, Differential White Blood Cell, Drug treatments